Teachers' Pedagogical Beliefs in a Project-Based Learning School in South Africa - Sizwe Errol Nxasana; Juebei Chen; Xiangyun Du; Mahmood Ahmed Hasan (MDPI AG, 2023)
Pedagogical beliefs serve as important drivers for teachers' approaches to implementing innovative learning methods. To promote change in education processes, understanding teachers' perspectives of their teaching roles and beliefs and how they change in the shift from traditional teaching to constructivist learning in diverse learning contexts, is essential. This study provides an overview of various traditional and constructivist beliefs held by teachers in a South African K-12 institution where project-based learning has been applied at the institutional level. The results indicate that pedagogical development and supportive policy at the institutional level both have a considerable influence on teachers' changes of beliefs; nevertheless, a sustainable change demands long-term efforts. Proposals for future pedagogical training design are suggested to help teachers move from traditional teaching beliefs to constructivist learning beliefs.